Predicting progression from mild cognitive impairment to Alzheimer's disease using longitudinal callosal atrophy. Issue 1 (8th March 2016) - Lee, Sang Han; Bachman, Alvin H.; Yu, Donghyeon; Lim, Johan; Ardekani, Babak A.; ,
Abstract: Introduction: We investigate whether longitudinal callosal atrophy could predict conversion from mild cognitive impairment (MCI) to Alzheimer's disease (AD). Methods: Longitudinal (baseline + 1‐year follow‐up) MRI scans of 132 MCI subjects from the Alzheimer's Disease Neuroimaging Initiative were used. A total of 54 subjects did not convert to AD over an average (±SD) follow‐up of 5.46 (±1.63) years, whereas 78 converted to AD with an average conversion time of 2.56 (±1.65) years. Annual change in the corpus callosum thickness profile was calculated from the baseline and 1‐year follow‐up MRI. A logistic regression model with fused lasso regularization for prediction was applied to the annual changes. Results: We found a sex difference. The accuracy of prediction was 84% in females and 61% in males. The discriminating regions of corpus callosum differed between sexes. In females, the genu, rostrum, and posterior body had predictive power, whereas the genu and splenium were relevant in males. Discussion: Annual callosal atrophy predicts MCI‐to‐AD conversion in females more accurately than in males.